Actividades lúdicas para el desarrollo cognitivo en niños de segundo año de la Educación General Básica - Arias Palma, Marielena del Carmen (2025)
This research analyzes the influence of playful activities on the cognitive development of students in the second grade of Basic General Education (EGB). Cognitive development in childhood is essential to consolidate skills such as attention, memory, logical reasoning and problem solving, essential pillars for learning. However, it was evident that many educational institutions still do not integrate recreational activities with a clear pedagogical purpose. Under a qualitative approach and a descriptive scope, techniques such as interviewing a teacher and direct observation of second-grade students were applied, in order to know the reality of educational practice around the use of play as a didactic strategy. The results revealed a low planning of structured play activities, which limits their impact on the children's mental processes. In response, a pedagogical proposal was designed with recreational activities aimed at enhancing key cognitive functions. It is concluded that recreational activities, correctly applied, constitute an effective tool to stimulate cognitive development and improve the quality of learning in basic education.